2010
DOI: 10.1111/j.1365-2230.2009.03774.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclin D1 and p16 in psoriasis before and after phototherapy

Abstract: Cyclin D1 upregulation and p16 downregulation may play a role in the pathogenesis of psoriasis. Normalization of the levels of both parameters may be a mechanism by which phototherapy induces remission in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
3
8
1
1
Order By: Relevance
“…Indeed, the results of the present study support this, as transfection of keratinocytes with Wnt5a siRNA suppressed cell proliferation and induced apoptosis. Wnt5a knockdown downregulated the expression of PCNA and MKI67 , proliferation markers that can be used to assess epidermal hyperproliferation in psoriasis and malignancy potential for in cutaneous lesions [19], as well as cyclin D1, which is a key regulator of cell cycle progression in psoriasis lesions [20]. These results are in contrast to those reported by Gudjonsson et al [9], who found that exogenous Wnt5a suppressed the growth of keratinocytes.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, the results of the present study support this, as transfection of keratinocytes with Wnt5a siRNA suppressed cell proliferation and induced apoptosis. Wnt5a knockdown downregulated the expression of PCNA and MKI67 , proliferation markers that can be used to assess epidermal hyperproliferation in psoriasis and malignancy potential for in cutaneous lesions [19], as well as cyclin D1, which is a key regulator of cell cycle progression in psoriasis lesions [20]. These results are in contrast to those reported by Gudjonsson et al [9], who found that exogenous Wnt5a suppressed the growth of keratinocytes.…”
Section: Discussioncontrasting
confidence: 56%
“…Abou et al studied the effect of phototherapy on the p16 expression and found that significantly less protein in psoriatic lesions were observed before phototherapy than in controls. Moreover, they confirmed the stimulating effect of phototherapy on the synthesis of the p16 in the skin [24]. In contrast, Elias et al showed elevated levels of the p16 protein in psoriatic plaque [21].…”
Section: The Role Of the P16 Protein In Psoriasis And Neoplastic Tranmentioning
confidence: 79%
“…In the light of recent studies, a decreased p16 level could be highly disadvantageous in psoriasis. A low level of p16 may contribute to epidermal proliferation and be involved in the pathogenesis of psoriasis [22,24]. Moreover, it seems that the p16 plays an important role in cell defense against mutagenic agents and could be responsible for the delayed apoptosis and the relative resistance to malignant transformation [12,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…most probable explanation for this apparent paradox is that the drug can slow down the cell division process by interfering with cell cycle controllers. In fact, it has been demonstrated that, after PUVA therapy, there are changes in cell cycle controlling proteins levels in the patients (Abou El-Ela et al, 2010). The detailed mechanism of action of 8-MOP remains under investigation, but if this hypothesis is confirmed it could prevent side effects common in many antitumor drugs (Terada et al, 2015).…”
Section: Discussionmentioning
confidence: 95%